Energy balance and deoxidation status of electric arc furnace tapping processes. (9th August 2022) - Tian, Bohan; Zhu, Rong; Wei, Guangsheng; Li, Xin; Dong, Kai; Xu, Afan
ABSTRACT: The tapping online refining process, in which carbon powder is injected into the tapping flow, has been proposed as a way to reduce the alloy burning loss in the electric arc furnace (EAF) tapping process. In this study, the deoxygenation reaction and mass-energy balance in the EAF tapping process are modelled with the help of plant data. On the basis of this mathematical model, deoxidation is analysed in the conventional and tapping online refining processes. The latter can reduce the amount of oxygen that reacts with the deoxidizer in the atmosphere by 9.84% and deoxidation amount of the alloy by 27.8%. As a result, the yield rates of Si, Mn, and Al increased by 5.34%, 27.21%, and 1.79%, respectively. Increasing the amount of carbon injection can further reduce the deoxidation amount of the alloy, but only when the amount of injected carbon is less than 1.2 kg tsteel −1 .